Экспериментальное применение моделей и технологий обеспечения качества для разработки компонентного программного решения реального времени - Земляной, Андрей Александрович (НТУ "ХПИ", 2013)
A technology for quality assurance of some real-time software quality attributes is considered. An experimental example of applying suggested technologies is provided. The example in cludes defining the solution architecture and quality requirements, using the prototype for statistics collection, analysis of the results.
Keywords: технология прототипирования; архитектура; сбор данных; обеспечение программное